Promoting the Use of Visiting Nurse Services for Patients Discharged From Hospital: Evaluation of a Japanese Municipality's Model Project. (May 2015) - Nagata, Satoko; Ogawa, Kaoru; Taguchi, Atsuko; Naruse, Takashi; Murashima, Sachiyo; Magilvy, Joan Kathy
A project to encourage the adequate use of visiting nurse services (VNS) after discharge was conducted by "K" City, Japan. Eligible individuals were inpatients of general hospital ready for discharge and assessed as potentially needing VNS, and their out-of-pocket fees for VNS within 1 month following discharge were covered by the city. To clarify this project's effect, patient/family's intention to use VNS and the utilization of VNS at each time point were evaluated. Eighty-eight residents used the project. Before initial hospitalization, less than one quarter of users had recognized the necessity of VNS. Many participants (88.6%) continued to use VNS even after the completion of the project period despite having to cover the VNS cost by themselves, indicating that this project had a positive impact on appropriate VNS use.